2013
DOI: 10.3109/17453674.2013.854665
|View full text |Cite
|
Sign up to set email alerts
|

No superior performance of hydroxyapatite-coated acetabular cups over porous-coated cups

Abstract: Background and purposeHydroxyapatite (HA) coating is believed to improve bone-implant ingrowth and long-term survival of prostheses. Recent studies, however, have challenged this view. Furthermore, HA particles may produce third-body wear and initiate aseptic loosening of implants. We report the performance of HA- and porous-coated acetabular cups in a prospective randomized trial.MethodsThis was an 8-year follow-up study of our previously published prospective randomized study to compare clinical outcomes, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…In accordance with studies on plasma-sprayed HA coatings we found little or no positive effect of electrochemically applied HA coating on migration of hemispherical cups after 2 years (Rohrl et al 2004, Valancius et al 2013. Our findings also indicate no improved long-term survival effect of electrochemically applied HA coating.…”
Section: Rsasupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with studies on plasma-sprayed HA coatings we found little or no positive effect of electrochemically applied HA coating on migration of hemispherical cups after 2 years (Rohrl et al 2004, Valancius et al 2013. Our findings also indicate no improved long-term survival effect of electrochemically applied HA coating.…”
Section: Rsasupporting
confidence: 91%
“…Plasma-sprayed HA coating results in better bony ingrowth and early implant fixation in experimental studies (Soballe et al 1992, Daugaard et al 2010). However, clinical results have not truly been able to show superior cementless cup fixation with HA over porous coating at midterm (Rohrl et al 2004, Valancius et al 2013 or long-term (Otten et al 2016, Lazarinis et al 2017.…”
mentioning
confidence: 99%
“…Although BMD did recover and stabilise in all zones, it remained significantly lower at follow-up than the baseline values [5]. Additionally, osteoconductive coating, such as hydroxyapatite [12] or alumina-reduced surface finish [13], did not improve peri-acetabular bone remodelling around modular cups. These data suggest that rigid acetabular fixation results in a loss of BMD in all zones over time and that this loss cannot be recovered by increasing the osteointegration properties of modular acetabular cups.…”
Section: Discussionmentioning
confidence: 80%
“…Although BMD did recover and stabilise in all zones, it remained signi cantly lower at follow-up than the baseline values [5]. Additionally, osteoconductive coating, such as hydroxyapatite [13] or alumina-reduced surface nish [14], did not improve peri-acetabular bone remodelling around modular cups. These data suggest that rigid acetabular xation results in a loss of BMD in all zones over time and that this loss cannot be recovered by increasing the osteointegration properties of modular acetabular cups.…”
Section: Discussionmentioning
confidence: 85%